The synthesis and characterization of styrene-grafted epoxidized natural rubber (ENR50-PS) by gradient HPLC analysis - Van Zyl, Andries Jakobus Petrus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.